2020
DOI: 10.1016/j.metop.2020.100030
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating FGF-21 levels in the first week of life and postnatal growth in hospitalized preterm infants

Abstract: Background The role of fetal and neonatal growth in the development of adult-onset diseases such as obesity and metabolic syndrome has become increasingly appreciated. Fibroblast growth factor-21 (FGF-21) is known as a regulator of glucose and lipid metabolism. FGF-21 levels are elevated in obese adults and children. The role of FGF-21 in neonatal growth in preterm infants is not known. Objectives We aimed to evaluate the association of circulating FGF-21 levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…FGF21 has previously been shown to be elevated in individuals with obesity, MASLD, and T2D, 30 and studies in newborn infants suggest that FGF21 is involved in early growth and development. 31 HAOX1 is a liver-specific peroxisomal enzyme, and emerging evidence has linked it to chronic liver disease. 32 Leptin is a key player in fat mass regulation and appetite control, and it has been implicated in the regulation of early adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 has previously been shown to be elevated in individuals with obesity, MASLD, and T2D, 30 and studies in newborn infants suggest that FGF21 is involved in early growth and development. 31 HAOX1 is a liver-specific peroxisomal enzyme, and emerging evidence has linked it to chronic liver disease. 32 Leptin is a key player in fat mass regulation and appetite control, and it has been implicated in the regulation of early adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this growth factor increases energy expenditure and core temperature likely via induced FFA catabolism and perhaps through thermogenic activation of brown adipocytes [ 91 ]. Liver-derived FGF21 is capable of activating thermogenesis in neonatal brown fat cells, and it is highly expressed in adults BAT [ 92 ]. A study examining the circulating levels of FGF21 showed that mild cold exposure increased the level of this transcriptional factor of browning which is associated with intensified BAT activation.…”
Section: Cold Bat Activationmentioning
confidence: 99%
“…In full-term infants, FGF21, synthesized in the liver [ 27 ], is induced from postnatal day 2 through the first year [ 28 ]. However, in preterm infants, circulating levels of FGF21 are below the lower limit of quantitation (LLOQ) of the assay in 85% of preterm infants at birth (cord blood), and in 31%, and 25% at 1 and 3 weeks, respectively [ 29 31 ]. Interestingly, FGF21 levels in the first 24 h positively correlate with infant weight and length Z-scores at discharge [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in preterm infants, circulating levels of FGF21 are below the lower limit of quantitation (LLOQ) of the assay in 85% of preterm infants at birth (cord blood), and in 31%, and 25% at 1 and 3 weeks, respectively [ 29 31 ]. Interestingly, FGF21 levels in the first 24 h positively correlate with infant weight and length Z-scores at discharge [ 31 ]. In the offspring of pregnant women with normal glucose tolerance, cord blood FGF21 levels also positively correlate with postnatal growth of infants [ 32 ].…”
Section: Introductionmentioning
confidence: 99%